EP668 Cancer in pregnancy: a 15-year descriptive analysis of 86 consecutive patients. (1st November 2019) - Di Loreto, E; Castellani, C; Buonomo, B; Polverino, G; Grossi, E; Buggio, L; Ossola, MW; Passera, S; Cribiù, M; Blundo, C; Peccatori, F; Scarfone, G
Abstract : Introduction/Background: The maternal diagnosis of cancer complicates approximately 0, 1% of all pregnancies. The most frequently diagnosed malignancies are breast cancer, cervical cancer, lymphoma, ovarian cancer and melanoma. Although chemotherapy can be administered during pregnancy, its effects on obstetric and neonatal outcome are still largely unknown. The aim of this study is to describe the oncologic management as well as the obstetric and perinatal outcomes in a consecutive series of patients with cancer during pregnancy. Methodology: We provided descriptive oncologic, obstetric and neonatal data from a cohort of pregnant patients diagnosed with primary invasive cancer between August 2004 and April 2019, retrospectively collected from clinical databases of IRCCS Policlinico di Milano and Istituto Europeo Di Oncologia (Milan, Italy). Results: We observed 86 consecutive patients with a diagnosis of malignancy during pregnancy: breast cancer was the most common type (70, 9%), followed by lymphomas (11, 6%). Patients with ongoing or missing oncological, obstetrical or neonatal data were excluded. Of the 62 eligible patients, 12, 9% received surgical treatment, 24% chemotherapy and 54, 8% a combination of both. For almost all pregnancies, timing of delivery was previously planned: 38% with labor inductions and 54% with elective cesarean sections, at a mean gestational age of 36 weeks. All pregnancies ended in a livebirth. Half of deliveries were preterm, mainly iatrogenic due to obstetric or oncologic indications: 3.2% were very low preterm, 6, 4% moderate preterm and 45% late preterm. The frequency of small for gestational age (birthweight <10° percentile) was 11.2%. Conclusion: This study confirms a high overall frequency of premature birth in pregnant patients with cancer, showing a lower rate of small for gestational age than described in literature. In order to have a better assessment of the toxicity of chemotherapy during pregnancy, we are currently investigating its fetal sequelae through histologic analysis of placental tissue and pediatric follow-up. Disclosure: Nothing to disclose.